Geographic variation in external morphology of North Pacific and Southern Hemisphere blue whales (Balaenoptera musculus) - Gilpatrick Jr., James W.; Perryman , Wayne L. (J. Cetacean Res. Manage., 2023)
Geographic variations in size and proportions of blue whales (Balaenoptera musculus) were investigated using length data acquired from whaling records and aerial photogrammetric surveys. Results showed that blue whales found in the eastern Pacific off Central and North America are significantly shorter (by approximately 2m) than blue whales found at higher latitudes in the North Pacific. Results support the occurrence of a morphologically distinct eastern North Pacific (ENP) blue whale population which migrates in spring/summer from warm waters off Central America and Mexico to temperate feeding grounds along the west coast of North America. Southern Hemisphere blue whales sampled with vertical aerial photogrammetry off northern Peru and the Galapagos Islands were similar in size to the ENP blue whales. However, the population affinity of these southern blue whales remains uncertain. No length data were available for blue whales formerly captured off southern Japan and Korea. Nonetheless, a history of diminishing fishery catches and a lack of any recent sightings suggests that these whales were members of a geographic population that is now severely depleted or extinct. Based on comparisons of total length, length of rostrum and length of tail region, ENP blue whales were found to be morphologically similar to the ‘pygmy’ blue whale (B.m. brevicauda) described from the Kerguelen Island region of the southern Indian Ocean. ‘Antarctic’ blue whales (B.m. intermedia) from the Southern Ocean were found to be statistically significantly larger than their conspecifics at high latitudes in the North Pacific. These results support the hypotheses that blue whales that migrate from warm seas to cold feeding grounds in high latitudes are larger than those whose distributions are limited to low and mid-latitudes. Differences in morphology may reflect selective pressure on populations to adapt physiologically to energy demands associated with different migration, environmental and ecological regimes. As some of the results come from populations located far apart in different oceans, questions remain concerning the continuity of populations within and among ocean basins. Consequently, research using fishery data and approaches such as photogrammetry, telemetry, acoustics and molecular genetic analysis should be continued to better understand the worldwide blue whale population structure.